2008
DOI: 10.1373/clinchem.2007.093005
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical Factors Affecting RIA Measurement of Plasma Kisspeptin

Abstract: Kisspeptins are peptide products of the KiSS-1 metastasis-suppressor (KISS1) gene and the natural ligands of the G-protein-coupled receptor GPR54. KISS1 was initially investigated as an antimetastasis gene. More recent studies have demonstrated that the kisspeptins are potent stimula

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…This was also true for each tumour subtype and indicates that a substantial and measurable systemic Kiss-10 expression even exists in patients with a low tumour burden as observed in this study. These findings are in line with the current literature in which elevated levels of Kisspeptin were found in tumour patients and low levels in controls were found most probably because of an inactivated kisspeptin system [26] .…”
Section: Discussionsupporting
confidence: 93%
“…This was also true for each tumour subtype and indicates that a substantial and measurable systemic Kiss-10 expression even exists in patients with a low tumour burden as observed in this study. These findings are in line with the current literature in which elevated levels of Kisspeptin were found in tumour patients and low levels in controls were found most probably because of an inactivated kisspeptin system [26] .…”
Section: Discussionsupporting
confidence: 93%
“…Samples were centrifuged immediately (3000 rotation per minute), separated and stored at À20 C until measurement of kisspeptin immunoreactivity using a previously described, in-house radioimmunoassay based on a sheep GQ2 antibody. 6 Assay sensitivity was 2pmol/L, and the intra-and inter-assay coefficients of variation were 8.3% and 10.2%, respectively.…”
Section: Methodsmentioning
confidence: 93%
“…Measurements using a commercially available assay suggested that the intravenous administration schedule used in our in vivo experiments produced increases in plasma kisspeptin (9 nmol/l) of the same order of magnitude as the physiological increases (2.5 nmol/l) reported in pregnant women [19], suggesting that there are circumstances where circulating kisspeptin could influence islet function. However, some caution is required in interpreting these data, since plasma kisspeptin can be difficult to measure accurately [35]. In the current study we used a human kisspeptin assay because there are no available assays for rat kisspeptin and the inter-species specificity of the assay is unknown.…”
Section: Discussionmentioning
confidence: 99%